The Renunciation of Wealth as a Rite of ‘the poor' and ‘perfect’: Bede and his Successors - Guiliano, Zachary (Studies in church history, 2023)
The renunciation and abandonment of wealth are rarely described as Christian rites of passage. Yet, for many medieval commentators on Scripture, such as the Venerable Bede and his successors, they were necessary rites, preliminaries to entry into the kingdom of heaven and into the class of ‘the perfect’. This article explores Arnold van Gennep's description of rites of passage in conjunction with the discussion of poverty in the Western exegetical tradition, centred in particular on Jesus's statements about poverty in Luke. It focuses on Bede's models of renunciation and abandonment of wealth which influenced Latin theology at least until the Reformation. The renunciation and abandonment of wealth provide an excellent test case for exploring van Gennep's ritual framework and its utility within the discipline of ecclesiastical history.